High growth rate and high wet etch resistance silicon nitride grown by low temperature plasma enhanced atomic layer deposition with a novel silylamine precursor. Issue 37 (8th September 2020) - Kim, Harrison Sejoon; Hwang, Su Min; Meng, Xin; Byun, Young-Chul; Jung, Yong Chan; Ravichandran, Arul Vigneswar; Sahota, Akshay; Kim, Si Joon; Ahn, Jinho; Lee, Lance; Zhou, Xiaobing; Hwang, Byung Keun; et al.
Abstract : Trisilylamine homolog, tris(disilanyl)amine (TDSA), is introduced as a novel precursor for the deposition of highly etch resistant silicon nitride thin films having a high growth rate at a low temperature (<300 °C) using plasma enhanced ALD process. Abstract : Trisilylamine (TSA), an exemplary chlorine and carbon-free commercial silylamine precursor, is well-known to induce improvements in the process and properties of silicon nitride (SiN x ) thin films grown using atomic layer deposition (ALD). Herein, we report a TSA homolog, tris(disilanyl)amine (TDSA), as a novel chlorine and carbon-free precursor for the deposition of highly etch resistant SiN x thin films having a high growth rate at a low temperature (<300 °C) using plasma enhanced ALD (PEALD) with hollow cathode plasma (HCP). These improvements in PEALD SiN x using TDSA may be attributed to higher surface reactivity of the molecule enabled by weaker Si–N bonds, higher molecular polarity and the existence of reactive Si–Si bonds in the molecule. The performance of PEALD SiN x grown by TDSA has been compared with that of TSA, aminosilanes and chlorosilanes, and explained with the structure–property relationship of the molecule. TDSA grows SiN x film faster than TSA. Furthermore, the TDSA precursor produces SiN x films that have lower wet etch rate (WER) when compared to other silylamine precursors like TSA, or other types of silane precursors such as aminosilanes and chlorosilanes. We believe that the result, that TDSA-grown SiN x films exhibit lower WER than TSA-grown SiN x films, can be attributed to the abundance of Si in SiN x films, which thereby offers high resistance to a wet etch.